Identity, development, and the politics of the past an ethnography of continuity and change in a coastal Ecuadorian community - Bauer, Daniel 1977- (University Press of Colorado, 2018)
"Combining personal narrative and ethnography, Bauer examines cultural change in a rural Ecuadorian village where community has worked to stake claim to an Indigenous identity in face of economic, social, and political integration. Bauer shows how villagers reconstructed their identity and ethnicity in a complex social matrix"...Provided by publisher